INVESTIGATING TRANSLATION METHODS AND TECHNIQUES IN RENDERING THE MAITREYA PANCASUTRA FROM CHINESE INTO INDONESIAN: A CASE STUDY - Sutarno Sutarno; Ida Ayu Gede Yadnyawati; Sulan Hermajayo; Vitalia Hanako Murni Simanjuntak; Herman Herman (Indonesian EFL Journal, 2026)
This study examines the methods and techniques employed in translating the Maitreya Pancasutra from Classical Chinese into Indonesian, with a focus on how linguistic and cultural complexities are managed. Using a qualitative descriptive approach, this research analyzes how complex linguistic and cultural elements of this sacred Buddhist text are transferred and adapted in translation. Data were collected via document analysis of the source (Classical Chinese) and target (Indonesian) texts, with particular attention to idiomatic expressions, doctrinal terminology, and culture-specific references that pose translation challenges. Using content analysis, the study identifies translation strategies and evaluates their effectiveness in maintaining both semantic fidelity and cultural resonance.,The findings reveal a patterned use of translation methods—including literal translation, borrowing, modulation, adaptation, and communicative enrichment—indicating a consistent strategic effort to preserve sacred terminology while enhancing narrative clarity for Indonesian readers. For instance, the phrase "如是我聞" was translated using a combination of semantic and communicative approaches, while sacred names like “彌勒” (Mílè) were retained through transliteration, reflecting doctrinal respect and the principle of the “Five Untranslatables.” Modulation and cultural approximation were applied to render abstract Buddhist concepts accessible to Indonesian readers, though sometimes leading to simplification of philosophical nuances. The use of adaptation, as in translating “仙人” as “Maharesi,” illustrates how translators navigate cultural gaps between source and target audiences. This study contributes to contemporary Buddhist translation studies by arguing that the Indonesian translation of the Maitreya Pancasutra adopts a hybrid strategy of doctrinal foreignization combined with linguistic and cultural domestication. It underscores the importance of culturally sensitive translation techniques in conveying religious texts meaningfully across linguistic and cultural boundaries.